Effect of the incorporation of SiC nanowire with double protective layers on SiC coating for C/C composites. Issue 11 (September 2023) - Xie, Aolin; Zhang, Bei; Ge, Yicheng; Peng, Ke; Xu, Ping; Wang, Xiaodong; Feng, Zhirong; Yi, Maozhong; Zhou, Zhe
Abstract: To maintain the thermal stability of SiC nanowires during SiC coating fabrication process, carbon and SiC double protective layers were covered on the surface of nanowires. And SiC nanowires with double protective layers toughened SiC coating were prepared by pack cementation. The results showed that after introducing the SiC nanowires with double protective layers, the fracture toughness of the SiC coating was increased by 88.4 %. The coating protected C/C for 175 h with a mass loss of 3.67 %, and after 51 thermal shock cycles, the mass losses of the oxidized coating were 3.96 %. The double protective layers are beneficial to improve the thermal stability of nanowires, leading to good fracture toughness and thermal shock resistance of SiC coating. SiC nanowires consume the energy of crack propagation by fracture, pullout and bridging, leading to an increase in fracture toughness.